2003
DOI: 10.1152/ajpheart.00111.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide regulates retinal vascular tone in humans

Abstract: The purpose of the present study was to investigate the contribution of basal nitric oxide (NO) on retinal vascular tone in humans. In addition, we set out to elucidate the role of NO in flicker-induced retinal vasodilation in humans. Twelve healthy young subjects were studied in a three-way crossover design. Subjects received an intravenous infusion of either placebo or NG-monomethyl-L-arginine (L-NMMA; 3 or 6 mg/kg over 5 min), an inhibitor of NO synthase. Thereafter, diffuse luminance flicker was consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
175
5
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(198 citation statements)
references
References 41 publications
12
175
5
3
Order By: Relevance
“…In a study with T1DM patients, a reduced retinal vessel response to flicker stimulation was observed, while retinal vascular reactivity after exogenous NO was not altered. 20 In a study by Dorner and colleagues, 13 it was found that approximately 50% of the flicker light-induced increase in retinal arteriolar and venular vasodilatation can be blocked by L-NG-monomethyl arginine citrate infusion. Two studies have shown that the retinal microvascular response to flicker light is impaired under certain pathological conditions such DM 21,22 or essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with T1DM patients, a reduced retinal vessel response to flicker stimulation was observed, while retinal vascular reactivity after exogenous NO was not altered. 20 In a study by Dorner and colleagues, 13 it was found that approximately 50% of the flicker light-induced increase in retinal arteriolar and venular vasodilatation can be blocked by L-NG-monomethyl arginine citrate infusion. Two studies have shown that the retinal microvascular response to flicker light is impaired under certain pathological conditions such DM 21,22 or essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…3,44,45 Of these agents, NO, generated constitutively by eNOS, has a key role in maintaining the basal vasodilator tone in ocular arteries. 40,[46][47][48][49][50][51][52] The major contribution of NO to vascular tone in human ocular vasculature is demonstrated by the observation that systemic administration of an NOS inhibitor reduced blood flow in the ONH [53][54][55] and by the involvement of NO in the POAG-related vascular conditions, such as hypertension, hypotension, and vasospasms. 56 Evidence of abnormal NO production in glaucoma is also provided by genetic studies.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42]46 However, other studies have shown a decrease in retinal blood flow with NOS inhibition. [21][22][23][24] Although, NO functions as a vasodilator and has been shown to control the basal arteriolar tone in the inner retina, 47 the presence of a retinal tissue-derived vasorelaxant 48,49 may counteract the effect of NOS inhibition, yielding a lack of alteration in the retinal vasculatures pO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of the system for determining pO 2 changes separately in the retinal and choroidal vasculatures was established by varying the fraction of inspired oxygen in rats. Furthermore, because inhibition of nitric oxide synthase (NOS) has been shown to be associated with decreased blood flow in the choroid and, to a lesser degree, in the retinal vascular bed, [16][17][18][19][20][21][22][23][24] this model was also used in the current study to establish the feasibility of our system for measuring chorioretinal pO 2 changes.…”
Section: Introductionmentioning
confidence: 99%